2017
DOI: 10.1002/agr.21546
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the livestock mandatory reporting act on the vertical price transmission within the beef supply chain

Abstract: This study examines the characteristics of price transmission along the vertical linkage in the beef industry before and after the implementation of the Mandatory Price Reporting Act (MPR) using econometric procedures such as the Gregory-Hansen structural break test, threshold autoregressive model, threshold error correction model, and nonlinear impulse response functions. Results show the improved speed of price adjustment after the MPR in the supply chain of the beef industry, whereas a limited evidence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…These results enabled to use the cointegration technique to calculate the relationship between international and domestic Mexican beef prices and between a processor and farm beef prices. These results concur with previous studies concerning the non-stationarity of beef prices (21,22,23) .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results enabled to use the cointegration technique to calculate the relationship between international and domestic Mexican beef prices and between a processor and farm beef prices. These results concur with previous studies concerning the non-stationarity of beef prices (21,22,23) .…”
Section: Resultssupporting
confidence: 93%
“…The ADF test on the error term shows a test statistic of -2.57 vs a 5 % critical value of -2.87, which indicates a failure to reject the null of non-stationarity. Different authors (21,22,23) reported similar results for beef prices. For the vertical model (equation 6), it was found an R 2 of 0.68, a t-statistic of 27.47, and an F statistic of 742.4.…”
Section: Long Run Cointegrationsupporting
confidence: 53%
“…Fousekis, Katrakilidis and Trachanas (2016) applied a nonlinear autoregressive distributed lag model to monthly U.S. beef price data and found evidence of price asymmetry from farm to wholesale and from wholesale to retail markets. Chung, Rushin and Sarathkal (2017) contrasted price transmissions before and after the implementation of the Livestock Mandatory Reporting Act and found limited evidence of increasing asymmetric price responses in the post-Act period. The four aforementioned studies have advanced the vertical price transmission literature by applying more complex methods.…”
Section: Related Literaturementioning
confidence: 98%
“…Frey and Manera (2007) and Meyer and von Cramon-Taubadel (2004) provide comprehensive surveys of the empirical literature on agricultural commodity price asymmetry, classifying and comparing heterogeneous studies in terms of econometric models employed, type of asymmetries tested and findings. More recent studies dealing with asymmetric price transmission in the U.S. beef supply chain are Boetel and Liu (2010), Emmanouilides and Fousekis (2015), Fousekis, Katrakilidis and Trachanas (2016), and Chung, Rushin and Sarathkal (2017). Boetel and Liu (2010) examined wholesale and retail price relationships in the beef and pork markets by accounting for possible structural breaks in the data.…”
Section: Related Literaturementioning
confidence: 99%